Study on the vertical well seepage model in composite carbonate reservoirs - Minjing, Chen; Zhan, Qu; Jiajun, Cao; Junhang, Hu; Xinggang, Meng; Shuaihu, Jia; Chenyu, Zhang (Frontiers in Earth Science, 2023)
Carbonate reservoir widely distributed throughout the world. Due to the good physical properties of the reservoirs, they are easy to be contaminated by mud during drilling opening, so they are often put into production after acidification. After acidification, the near-well reservoir physical property is improved, while the far-well reservoir physical property remains unchanged. Such reservoirs are commonly called composite reservoirs. Composite carbonate reservoir seepage law is more complicated. In this paper, the point source function of triple-medium composite reservoir is established by using the source function theory, Laplace transform, perturbation transform and linear superposition principle of partial differential equation. Secondly, the vertical well seepage model of composite reservoir is obtained through the new point source function. Finally, the correctness of the model is verified, and the sensitivity analysis of the key parameters affecting the seepage law is carried out. The applicability of the model established in this paper is demonstrated by two wells in the field. This paper provides a theoretical basis for vertical well test analysis of composite reservoirs.